2013
DOI: 10.7754/clin.lab.2012.120110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Chlorella vulgaris Supplementation on the Modulation of Oxidative Stress in Apparently Healthy Smokers

Abstract: Background: Smoking is among the established yet modifiable risk factors for cancers, cardiovascular diseases, and pulmonary disorders. Oxidative stress has been proposed as a key mechanism mediating the deleterious consequences of smoking. The present study evaluated the effect of supplementation with Chlorella vulgaris, a nutrient and bioactive green microalgae with proven antioxidant capacity, on the burden of oxidative stress in Iranian smokers. Methods: Thirty-eight smokers (mean age: 37.11 ± 1.69 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
(42 reference statements)
2
13
0
5
Order By: Relevance
“…The study is supported by rodent model studies of Yuan and Walsh [27] which demonstrated the protective effects of dietary kelps and other red and green algae against mammary, intestinal and skin carcinogenesis. Recent studies suggest C. vulgaris as an effective natural chemotoxic agent against tumour cells by inducing apoptosis [28] . Chlorella PR1 efficiently reduced murine melanoma B16F10 cells viability by 50% with 5.5 µg/ml concentration of DMSO extract [29] .…”
Section: Resultsmentioning
confidence: 99%
“…The study is supported by rodent model studies of Yuan and Walsh [27] which demonstrated the protective effects of dietary kelps and other red and green algae against mammary, intestinal and skin carcinogenesis. Recent studies suggest C. vulgaris as an effective natural chemotoxic agent against tumour cells by inducing apoptosis [28] . Chlorella PR1 efficiently reduced murine melanoma B16F10 cells viability by 50% with 5.5 µg/ml concentration of DMSO extract [29] .…”
Section: Resultsmentioning
confidence: 99%
“…6). Несмотря на многочисленные исследования, в которых были показаны антиоксидантные и противовос-палительные свойства хлореллы, противоопухолевые или другие положительные эффекты на организмы животных или человека (Vijayavel et al, 2007;Wang et al, 2010;Panahi et al, 2012aPanahi et al, , b, 2013Kim et al, 2015;Kubatka et al, 2015), работы по влиянию микроводорослей на поведение практически отсутствуют. Тем не менее при исследовании эффектов хлореллы, которую использовали как дополне-ние к стандартной схеме терапии антидепрессантами па-циентов с диагнозом Большое депрессивное расстройство (БДР), характеризующееся в том числе утратой интересов, снижением энергичности и повышенной утомляемостью, была показана ее эффективность (Panahi et al, 2015).…”
Section: Discussionunclassified
“…In addition, C. vulgaris dry extracts may modulate oxidative damage in chronically stressed individuals. A study providing 3600 mg/day (six weeks) dry C. vulgaris extract to non-comorbidity bearing smokers showed significant decrease in lipid peroxidation and optimized antioxidant status of participants [36]. Other Chlorella species (C. pyrenoidosa) were also shown to be beneficial for the treatment of signs and symptoms, specifically of fibromyalgia, hypertension, and ulcerative colitis.…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%
“…As indicated by previous studies, Chlorella may be used as a dietary antioxidant [36,42]. In a recent work, patients (n=30) with non-alcoholic liver steatosis were supplemented with 400 mg/day vitamin E and 1200 mg/day C. vulgaris extract.…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%